Quercetin Solid Lipid Microparticle Stability and Deposition in Rat Lungs: A Study of Surfactant Effect - Hariyadi, Dewi Melani; Sairiyah, Siti Nasikatus; Rahman, Fakhrinnisa Wildani; Rijal, Muhammad Agus Syamsur; Rosita, Noorma; Rahmadi, Mahardian (Science and Technology Indonesia, 2024)
This study aims to determine the effect of surfactant concentration on Quercetin SLM as a potential carrier of respiratory diseases, especially ones resulting from oxidative stress injury. Quercetin is a natural antioxidant with high activity. SLM was formed with 5% compritol 888 ATO as a lipid and different concentrations of poloxamer 188 as a surfactant. SLM was produced by a combination of emulsification and sonication involving freeze drying. SLM is characterized by organolepsis, morphology, yield, particle size, drug loading, and entrapment efficiency. The antioxidant activity of quercetin SLMs was tested using the ABTS method. SLMs are characterized as having round and smooth morphology, high yield (F1 88.53%; F2 91.44%; F3 92.87%); particle size (F1 1.81 um; F2 1.90 um; F3 1.94 um); high drug loading (F1 15.96%; F2 13.74%; F3 13.19%); and high entrapment efficiency (F1 96.53%; F2 87.94%; F3 87.48%). Increasing surfactant concentration did not produce a significant difference between formulas. Quercetin SLM showed high antioxidant activity (Quercetin 94.43%; F1 94.35%; F2 94.36%; F3 94.37%). SLM was stable at storage temperatures between 25°C and 40°C. The effect of surfactant can be seen on particle size, drug loading, and entrapment efficiency at 40°C. Results of in vivo deposition study indicated that all SLM formulas were able to deliver quercetin to the lungs. Increasing the concentration of surfactant in Quercetin SLMs made no difference to the lung deposition as confirmed by observations conducted at 1 hour and 4 hours. Quercetin SLM has the potential for lung delivery by inhalation.